Indonesian Tourism Village Award: Impact, Strategy, and Potential for Integrated Rural Tourism in Bali - Putu Devi Rosalina; I Wayan Wardika; Ni Made Prasiwi Bestari (Jurnal Kajian Bali (Journal of Bali Studies), 2024)
The Indonesian Tourism Village Award (ADWI) is part of the central government's commitment to stimulating the motivation of village communities to develop tourism. However, our understanding remains limited on how ADWI develop rural tourism. This present research analyses online news media, with a research question: How does ADWI impact tourism development in rural tourism destinations? Through thematic analysis, two positive impacts were found: Marketing and optimising tourism potential, with one negative impact: passive participation from the government. This article then discusses strategies for overcoming the negative impact and provides avenues for future research by reconceptualising the 4As framework for future studies on the tourism village potential. This research offers a theoretical contribution to the conceptualisation of the 4As in the context of rural tourism and, practically, provides advice to tourism village stakeholders in Bali to develop integrated rural tourism.